The use of essential oils based antiseptic solution in the treatment of denture stomatitis - Janjić-Pavlović Ognjenka; Stančić Ivica; Cicmil Smiljka; Stojanović Zorica; Lečić Jelena; Elenčevski Sašo (Serbian Medical Society - Dental Section, Belgrade, 2017)
Introduction Local therapy of denture stomatitis (DS) associated with Candida species fungi infection usually involves the application of nystatin and miconazole. Due to the fact that these drugs may be less efficient against biofilm and possible resistance development, a new approach in the treatment includes the use of antiseptic agents. The aim of the study was to compare clinical and microbiological therapeutic outcomes of antiseptic solution Listerine® and Daktanol® antifungal oral gel in the treatment of DS associated with Candida species fungi. Material and Methods The study included 30 patients affected by DS, divided into the two treatment groups, control group (n=15) treated by Daktanol® gel and experimental group (n=15) treated by the antiseptic solution Listerine®. Successful treatment was evaluated based on palatal mucosa inflammation reduction classified according to the Newton classification and the difference in the number of fungal colony- forming units (CFU) isolated by smears before and after the treatment that lasted 14 days. Results Reduction in inflammation intensity and fungal CFU number on palatal mucosa (p<0,01) as well as on denture base (p<0,01) were observed in both groups of subjects after the treatment. Conclusion Antiseptic solution Listerine® and Daktanol® antifungal gel both reduced palatal mucosal inflammation and CFU number of fungi in mouth without significant differences among them. CFU number of fungi isolated from denture base was significantly lower after the treatment with Listerine® (p<0.05).